First report of sporadic cases of Candida auris in Colombia. (April 2018) - Parra-Giraldo, Claudia M.; Valderrama, Sandra L.; Cortes-Fraile, Gloria; Garzón, Javier R.; Ariza, Beatriz E.; Morio, Florent; Linares-Linares, Melva Y.; Ceballos-Garzón, Andrés; de la Hoz, Alejandro; Hernandez, Catalina; Alvarez-Moreno, Carlos; Le Pape, Patrice
Highlights: The emerging fungus Candida auris is a serious global threat. It is often multidrug-resistant, It is a public health problem. Candida auris yeast is difficult to identify with standard laboratory tools, and it can be misidentified in labs without specific technology. Candida auris it has spread quickly and caused infections in more than a dozen countries this is the first reported with Candida auris in Colombia. Abstract: Background: Candida auris is a recently reported Candida species that is phenotypically similar to Candida haemulonii and related to hospital outbreaks. This organism can be misidentified as Candida haemulonii, Candida famata, Candida catenulata, or Rhodotorula glutinis by phenotypic approaches. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and DNA sequence analysis using internal transcribed spacer rDNA bar-coding provide an accurate identification. Case reports: Three cases of C. auris infection in patients with risk factors for fungal infection (one admitted to the intensive care unit, one with lymphoma, and one with HIV; all three with previous antibiotic use) are reported; these infections were not epidemiologically related. Yeast isolates were recovered from blood, ocular secretion, and bronchoalveolar lavage and were misidentified as C. catenulata and Candida albicans by the phenotypic MicroScan method. The isolates were confirmed to be C. auris by means of MALDI-TOF MS and DNA sequence analysis. Antifungal susceptibility testing was performed on these C. auris isolates, which exhibited high minimum inhibitory concentrations to triazoles and amphotericin B. One patient survived and the other two died. Only one of these deaths was related to fungemia. Conclusions: C. auris is an emerging and opportunistic multidrug-resistant human pathogen. It is necessary to strengthen measures to achieve an accurate and quick identification and also to avoid its dissemination. This will require improvements in health and infection control measures, as well as the promotion of antifungal stewardship in healthcare facilities.